Commercialisation of high energy density sodium-ion batteries: Faradion's journey and outlook. Issue 13 (9th March 2021) - Rudola, Ashish; Rennie, Anthony J. R.; Heap, Richard; Meysami, Seyyed Shayan; Lowbridge, Alex; Mazzali, Francesco; Sayers, Ruth; Wright, Christopher J.; Barker, Jerry
Abstract : The thinking behind Faradion's historical and current commercial Na-ion technology and the importance of some crucial experimental factors in battery research are discussed. Abstract : There is no doubt that rechargeable batteries will play a huge role in the future of the world. Sodium-ion (Na-ion) batteries might be the ideal middle-ground between high performance delivered by the modern lithium-ion (Li-ion) battery, desire for low costs and long-term sustainability. To commercialise the Na-ion technology, Faradion was founded in 2011 as the world's first non-aqueous Na-ion battery company. Over the years, we have made rapid progress in increasing the all-around performance of Na-ion batteries, benefitting from decades' worth of industry experience and prior Na-ion as well as Li-ion academic research. The Faradion Na-ion chemistry can now exceed the energy densities of LiFePO4 //graphite Li-ion batteries with rapidly converging cycle lives, similar rate performance and charge acceptance. In addition, our technology makes use of lower materials costs, offers improved safety through the use of high flash point electrolytes and has the ability to be discharged to zero volts for storage and transportation. In this article, Faradion's step-by-step progress in the Na-ion technology will be discussed together with a general picture of how our Na-ion chemistry compares with other Na-ion systems and commercially available Li-ion technology. Finally, the importance of starting experimental testing on new materials, keeping commercially-relevant protocols in mind, will be illustrated by clearly highlighting the drastic effects of some crucial experimental factors. By sharing such industry know-how, Faradion hopes researchers worldwide will adopt such experimental protocols as routine methodology in the laboratory. These simple measures can significantly shorten the path from a new invention to commercial application, while also ensuring that the battery-related literature conveys the true commercial feasibility of an invention or discovery to the general public.